Філософія війни і миру: антропоцентрична дихотомія любові/ненависті як мотивація героїзму (за "Листами до німецького друга" Альбера Камю) - Тарнашинська, Л.Б. (Слово і Час, 2019)
Розглядається гуманістично-антропоцентрична позиція французького письменника й філософа
А. Камю в “Листах до німецького друга” (1943 – 1944). Під час Другої світової війни письменник
пережив екзистенційну драму сумління, викликану ситуацією в окупованій Франції – країні, яка
все ж зуміла перетворити свою поразку на перемогу. Фашизм очима А. Камю розкрито в контексті
філософії війни/миру через низку опозитів (любов/ненависть, насильство/ненасильство, сила/
слабкість, героїзм/боягузтво, друг/ворог, свій/чужий, герой/зрадник, переможець/переможений).
Апеляція до ціни жертви/втрати/перемоги відбувається в силовому полі психології насильства/
ненасильства. Письменник гранично антропологізує проблему, ставлячи в центр “аргументів
сумління” людину з комплексом її цінностей. Антропоцентричний розтин ситуації опору/неопору
в умовах окупації виводить на історичні паралелі з новітньою історією та їх гуманістичні уроки. The article considers the humanistic anthropocentric position of the French writer and philosopher
A. Camus in his “Letters to a German Friend” (1943–1944). During the World War II the writer
experienced a real existential drama of conscience caused by situation in the occupied France. The
country experienced horror and humiliation of temporary occupation and managed to turn its defeat
into victory. Fascism in the eyes of the prominent humanist writer and philosopher of France is revealed
in the context of the philosophy of war/peace. This context is specified by a number of statements,
such as love/hate, violence/nonviolence, etc. ‘Disturbed Conscience’ of A. Camus, in spite of patriotic
reasons, sought intercourse between different pairs of opposition: strength/weakness, heroism/
cowardice, etc. The oppositions we/you, our/your appeal to such concepts as the price of sacrifice,
the price of loss, the price of victory.
The monological epistolary genre allows showing the psychological and moral reality of the war,
with possible shifts in time and appeal to the Other. A. Camus strengthens the existential problem, the
core of which is the opposition “Me – Other” (according to M. Buber and E. Levinas) and “Me like the
Other» (P. Ricker). In fact, he initiates a new ontological and linguistic reality embedded in the paradigm
of a new/other discourse of war. The binary oppositions similar/unrelated, friend/foe, one’s own/alien,
hero/traitor, winner/ defeated are being demounted in the field of psychology of violence reflected by
the author within the psychology of nonviolence. At the same time, the basic oppositional pair patriot/
collaborator is integrated into a complex system of psychological controversies being the ground of
Camus’ psychology of nonviolence. The writer expands a number of oppositional concepts adding
the dichotomy of ‘two Europes’. He anthropologizes the considered problems to the highest extent,
placing a man with the whole complex of human values in the center of his ‘arguments of conscience’.